Interleukin-6, C-reactive protein and interleukin-10 after antidepressant treatment in people with depression: a meta-analysis - Hiles, S. A.; Baker, A. L.; de Malmanche, T.; Attia, J. (Psychological medicine, 2012)
Cross-sectional studies support an association between depression and inflammatory markers. However, little is known of their relationship in the context of antidepressant treatment. Our aim was to explore via meta-analysis whether antidepressant treatment is associated with a reduction in three inflammatory markers associated with depression. A computerized search of EMBASE, Medline, PsycINFO and Cochrane Library databases was completed using subject headings for depression and either interleukin-6, C-reactive protein or interleukin-10, selecting studies which reported circulating levels of inflammatory markers before and after antidepressant treatment for people with depression. Outcome and moderator variables were coded for analysis, including inflammatory marker change, depression severity change, age, gender ratio, assay brand, treatment response and weight change. Pooled effect sizes showed a significant decrease in interleukin-6 (n=14, d=-0.42, p=0.02), marginally significant decrease in C-reactive protein (n=8, d=-0.57, p=0.05) and a non-significant decrease in interleukin-10 (n=3, d=-0.45, p=0.14) after treatment. High levels of heterogeneity were observed, which may be associated with clinical variations between the studies such as weight gain, anxiety, incomplete remission and other individual differences and co-morbidities. The findings of this meta-analysis indicate that there may be a normalization of overactive inflammatory processes following antidepressant treatment.